Short report on the excavations in 2013 of the Department of Hungarian Medieval and Early Modern Archaeology (Eötvös Loránd University, Budapest) - Maxim Mordovin (Dissertationes Archaeologicae: Ex Instituto Archaeologico Universitatis de Rolando Eötvös Nominatae, 2013)
The Department of Hungarian Medieval and Early Modern Archaeology carried out or participated at excavations on eight sites cooperating with several foreign institutions in 2013. These sites are Tusa – La Şanţuri (Romania), Văcăreşti – Sándor manor house (Romania), Fiľakovo – Dolný hrad (Slovakia), Zvolen – Dolný hrad (Slovakia), Čabraď Castle (Slovakia), Bánd – Essegvár (Hungary), Visonta (Hungary) and Drégely Castle (Hungary).